THE EFFECT OF LEADERSHIP AND COMPENSATION ON THE JOB SATISFACTION MEDIATED BY MOTIVATION AT PT. INDESSO CULINAROMA INTERNATIONAL - Dharmiarto, Rizki Iman; Iqbal, M. Ali; Saluy, Ahmad Badawi (Dinasti Publisher, 2021)
Job satisfaction is a measure of a positive feeling about work resulting from an analysis of the characteristics in a person. Based on job satisfaction assessment data, it was found that the phenomenon of employee job satisfaction at PT. Indesso Culinoma International is quite low, so it needs to be researched. Theapurpose of this study was to examine the effect of leadershipoand compensation on job satisfaction with motivation as a moderating variable at PT. Indesso Culinoma International. The technique used in this study is a survey method in the form of a questionnaire with a sample of all employees of PT. Indesso Culinoma International. The research design used associative and the data analysis technique used was path analyze using the smartPLS application. The results showed that leadership and compensation had a positive and significant effect on job satisfaction at PT. Indesso Culinoma International. In addition, motivational variables can also mediate the influence of leadership and compensation on job satisfaction.